Solvothermal Synthesis and Crystal Structure of A Supramolecular Compound Tris(tert-butylamino)chlorophosphonium Chloride - Shi, Hong-Sheng; Qian, Jin; Fan, Jing; Deng, Ni; Shu, Kangying (Asian Journal of Chemistry, 2012)
During the research of the reaction of OP(NHt-Bu)3 and ZnCl2 with hydrochloric acid in toluene, the crystal of the tris(tert-butylamino)chlorophosphonium chloride [ClP(NHt-Bu)3](Cl) (1) was obtained under solvothermal reaction condition. The single-crystal X-ray diffraction reveals the title compound crystallizes in space group P21/c (No. 14) with a = 15.280(3) Å, b = 9.2100(18) Å, c = 12.790(3) Å, a = 90 º, b = 93.19(3) º, g = 90º, V = 1797.1(6) Å3, Z = 4, Dc = 1.176 g cm-3, F(000) = 688, μ = 0.44 mm-1. The phosphorus atom of cation is located in the center of a tetrahedron constructed of a chloride atom and three N atoms of three NHt-Bu groups. The anion of Cl– is connected with a cation and adjacent cation through three N-H···Cl hydrogen bonds. And through these hydrogen bonds, a zig-zag supramolecular chain is formed, which array all along the c axis.